Crime victim and International Criminal Court: an undeniable model to the lawmaker - Teresa Lancry Robalo (Revista Brasileira de Direito Processual Penal)
This paper aims at having a closer look to the level of protection afforded by the Rome Statute to crime victims, as well by its Rules of Procedure and Evidence. The Rome Statute, which encompasses both substantial and procedural norms, has taken the Statutes and the decisions adopted by the ad hoc International Criminal Tribunals for ex-Yugoslavia and Rwanda. However, the latter did not provide a clear model that aimed at victims’ protection. Therefore, Rome Statute and its Rules of Procedure and Evidence added a set of central measures that aim at protecting victims and witnesses, giving them the opportunity to take part in the process and granting them proper reparation. It shows up as being a paradigm to be taken into account by the internal legislator, even if the State is not a member of the Rome Statute. Hence, the role played by the international community in this regard must be taken into account by the legislator, allowing the victim to regain a conflict that indeed belongs to him/her, as previously argued by Nils Christie. This study makes use of a qualitative methodology, essentially taking literature into deep consideration and starting from the study of the innovation brought by the International Criminal Court on this matter. It is the author’s aim to emphasize its importance as a potential model to be offered to the national legislator. Our hypothesis relies on the assumption that the model created by the Rome Statute towards victims has the potential to be considered by national legislator.